Wireless Sensor Networks Applications in Aircraft Structural Health Monitoring - Vujic, Dragoljub A (Journal of Applied Engineering Science, 2015)
Aircraft industry has to meet a challenge of reducing operational and maintenance costs. One of the possible ways for reducing these costs is the introduction of wireless sensor networks (WSNs). WSNs are already finding a variety of applications for both safety-critical and non-critical distributed systems. This paper deals with the application of WSNs for aircraft structural health monitoring. Special attention has been given to the WSNs design issues using available components on the market. A general sheme for aircraft structural health monitoring using MicroStrain components has been proposed.